Ingrouping, Outgrouping, and the Pragmatics of Peripheral Speech. Issue 4 (10th January 2017) - HERBERT, CASSIE; KUKLA, REBECCA
ABSTRACT: Speech does not merely reflect social identity; it helps create it, by ingrouping and outgrouping individuals and establishing and clarifying community boundaries and norms of membership. We define a pragmatic category of community-specific speech that is used by and directed at community insiders. We focus on a species of community-specific speech that has flown under the philosophical radar, a type of speech we term peripheral speech: Peripheral speech is informal, typically playful, insider speech that includes inside jokes, riffs, gossip, insider references; it is loosely constrained, and only those who have skills and normative competence characteristic of a community can play along successfully. Peripheral speech is shared by a community, but also used to bring people into it and cast people out of it. We argue that entitlement to peripheral speech requires a type of speaker authority that is not granted by way of established rules and conventions, but rather settled locally and in situ.